(untitled) (Olhar de Professor, 2022)
This article has as its object of study Strategy no. 12.7 of the Brazilian National Education Plan, which established that at least 10% of the study load of undergraduate courses must be allocated to public outreach, which challenges higher education institutions to rethink their outreach conceptions, historically marked by welfare actions outside the course curriculum. The objectives were to measure the tensions that accompany the trajectory of public outreach in Brazil and elucidate the possibilities of its integration into teacher training through an emancipatory praxis. This article, of a bibliographic nature, synthesized reflections about the history of the Brazilian education and public outreach and demonstrated that, by being integrated into the course curriculum, outreach expands the possibilities for critical teaching formation committed to social transformation. It is urgent, however, to propose interactions, based on outreach praxis, that reinforce its legitimacy as an indispensable element for the full realization of the university as an emancipatory instrument.